Mental Toughness and Stress Tolerance in Elite and Beginner Level Athletes - Shah, Drashti (My University, 2023)
Background and aim: The psychological variables of mental toughness and stress tolerance of athletes across different genders and experience levels have been of interest to researchers and it would be interesting to do a study studying these variables with a heterogenous pool of athletes from different experience levels and of different genders. This study aims to do exactly that. Methodology: Athletes (N=132) were selected from both genders (M=70, F=62) and divided into two experience levels i.e. beginner (N=66, M=33, F=33) and elite (N=66, M=37, F=29). Tools: They were administered the MTQ48 for studying the mental toughness variable and then were tested using the Determination Test on the Vienna Test System for finding out their reactive stress tolerance. Results & conclusions: The results indicate that elite female athletes had the highest scores in ‘correct (reactive stress tolerance)’ and ‘omitted (ability to sustain attention)’ variables of the DT. Elite males had the highest scores for the ‘incorrect (ability to concentrate)’ Significant effects of experience were observed for ‘incorrect’ and significant gender differences were observed in ‘mental toughness’. Elite male athletes had the highest scores in mental toughness as well.
Keywords: Mental toughness; Stress tolerance; Elite; Beginner; Gender; Determination test